2013
DOI: 10.1371/journal.pone.0059771
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of the CD163+ and CD68+ Macrophages in Patients with Hepatocellular Carcinoma

Abstract: Our previous study has found that the abundance of peritumoral CD68+ macrophages was associated with poor prognosis in hepatocellular carcinoma (HCC) after resection. However, CD68 staining could not discriminate the protumoral or tumoricidal subpopulations from pan-macrophages. CD163 is a marker of alternatively activated macrophages. In this study, the clinical significance of CD163+ cells in tumors and peritumoral liver tissues was evaluated in a cohort of 295 patients with HCC after curative resection. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 38 publications
5
60
1
1
Order By: Relevance
“…The expression of CD163 in lymphomas, carcinomas and sarcomas has been shown to be highly specific and largely restricted to the monocyte/macrophage lineage 36 . Furthermore, CD163-positive macrophages may in some cases outnumber CD68-positive cells 37,41 as indicated by our study. Many reports have used CD163 for identification of M2 macrophages 14,16,17,31,32 .…”
Section: Discussionsupporting
confidence: 66%
“…The expression of CD163 in lymphomas, carcinomas and sarcomas has been shown to be highly specific and largely restricted to the monocyte/macrophage lineage 36 . Furthermore, CD163-positive macrophages may in some cases outnumber CD68-positive cells 37,41 as indicated by our study. Many reports have used CD163 for identification of M2 macrophages 14,16,17,31,32 .…”
Section: Discussionsupporting
confidence: 66%
“…Several reports showed positive correlations between CD68 + TAM density and poor prognosis. [45][46][47] In contrast, the density of CD163 + M2-TAMs had no prognostic value. 47 A favorable association between CD68 + TAM density and DFS and OS was also reported.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 95%
“…[45][46][47] In contrast, the density of CD163 + M2-TAMs had no prognostic value. 47 A favorable association between CD68 + TAM density and DFS and OS was also reported. 48 With regard to the relationship between macrophages and metastasis, the density of CD68 + HLA-DR + M1-like TAMs in HCC cases with metastasis was reportedly significantly higher than in cases without metastasis.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 95%
See 1 more Smart Citation
“…[79][80][81] Except for evaluating tumorigenesis, TAM-associated CD68 expression levels can serve as a useful predictive marker for prognosis of survival of cancer patients. [82][83][84] In the phase III LYM-3001 study, Coiffier et al 85 showed a significant predictive value of a combination of low CD68 tumor expression and a genetic marker (proteasome subunit-β type-1 (PSMB1) PA11A G allele) for a longer progression-free survival of follicular lymphoma patients treated with bortezomib (proteasome inhibitor) and rituximab (anti-CD20 monoclonal antibody) vs treatment with rituximab alone. Indeed, these results suggest a potential role for assessment of CD68 expression in tumors to evaluate the efficiency and outcome prognosis of anticancer therapy.…”
Section: Cd68 In Cancermentioning
confidence: 99%